PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUASAN WISATAWAN NUSANTARA MENGGUNAKAN TRANSPORTASI ONLINE GRAB DI KUTA, BALI - Sendy Ludju, Maria Laru; Kusuma Negara, I Made; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
This study aimed to explain the effect of service quality and brand image on the satisfaction of domestic tourists who used Grab online transportation in Kuta, Bali. The research method used in this research was quantitative and qualitative research methods (mix methods). Questionnaires were distributed to 150 domestic tourists with a sample determination method using purposive sampling. The method of data analysis used multiple linear regression analysis with SPSS 18.0 program. The results of this study stated that partially the quality of service had a positive and significant effect on the satisfaction of domestic tourists with the dominant dimension being the tangible dimension and brand I mage giving a positive and significant effect on the satisfaction of domestic tourists with the dominating dimension being the support of the brand association. Simultaneously, the quality of service and brand image had a positive and significant influence on the satisfaction of domestic tourists. The R Square value of 0.672 meant that 67,2% of tourist satisfaction could be explained by the variable service quality and brand image, while the remaining 32,8% was influenced by other variables not examined in this study.